2019
DOI: 10.1016/j.jid.2019.05.017
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 Regulates Macrophage-Mediated Inflammation in Diabetic Wound Repair

Abstract: Control of inflammation is critical for the treatment of nonhealing wounds, but a delicate balance exists between early inflammation that is essential for normal tissue repair and the pathologic inflammation that can occur later in the repair process. This necessitates the development of novel therapies that can target inflammation at the appropriate time during repair. Here, we found that SIRT3 is essential for normal healing and regulates inflammation in wound macrophages after injury. Under prediabetic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 45 publications
(60 reference statements)
2
44
0
Order By: Relevance
“…Biopsy of patients suffering from systemic sclerosis (SSC) indicated that SIRT3 expression in skin significantly decreased compared with the healthy control . One latest study found that SIRT3 was decreased in wound macrophage via fatty acid‐binding protein 4 up‐regulation . Our present study also confirmed that that SIRT3 expression in diabetic skin significantly reduced.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Biopsy of patients suffering from systemic sclerosis (SSC) indicated that SIRT3 expression in skin significantly decreased compared with the healthy control . One latest study found that SIRT3 was decreased in wound macrophage via fatty acid‐binding protein 4 up‐regulation . Our present study also confirmed that that SIRT3 expression in diabetic skin significantly reduced.…”
Section: Discussionsupporting
confidence: 84%
“…Our study found that the total antioxidant capacity and SOD activity decreased while the MDA level increased in the wound with diabetes, which indicated that the disorder of hyperglycaemia metabolism impaired antioxidant system by weakening the ability of scavenging free radicals and aggravating lipid peroxidation. SIRT3 controls repair‐associated inflammation, which is beneficial to protect against excessive accumulation of ROS . Actually, oxidative stress having been indicated by DHE or MitoSOX staining in diabetes was further strengthened, which might be due to lack of SIRT3 in our study.…”
Section: Discussionmentioning
confidence: 59%
“…A successful wound closure requires a subtle collaboration between the skin cells and nonskin cells, such as blood cells, immune cells and stem cells. A recent mouse study found that SIRT3 plays an important role in wound repair, especially in wound macrophages (58). This study demonstrated significantly increased SIRT3 in wound macrophages during the transition from an inflammatory to a reparative stage.…”
Section: Role In Wound Healingsupporting
confidence: 59%
“…Wounds were then carefully minced with sharp scissors and digested by incubating in a solution of 50 mg/mL Liberase TM (Roche) and 20 U/mL DNase I (Milli-poreSigma). Because the final cell number is limited, wounds from the same genotype/treatment were pooled to maximize cell yield, as previously published (11,12,14,16,54,(57)(58)(59). Wound cell suspensions were then gently plunged and filtered through a 100-μm filter to yield a single-cell suspension.…”
Section: Methodsmentioning
confidence: 99%